2015
DOI: 10.1097/md.0000000000000491
|View full text |Cite
|
Sign up to set email alerts
|

Second and Third-look Endoscopy for the Prevention of Post-ESD Bleeding

Abstract: The efficacy of 2nd-look esophagogastroduodenoscopy (EGD) with endoscopic hemostatic therapy (EHT) for the prevention of postendoscopic submucosal dissection (ESD) clinical bleeding remains controversial. The aim of this study was to estimate post-ESD bleeding rate using 2nd and 3rd-look strategy, and to determine risk factors for clinical bleeding, and for EHT at 2nd and 3rd-look EGDs.Three hundred forty-four consecutive patients with early gastric cancer or adenoma underwent ESD from January 2006 through Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
1
10
2
Order By: Relevance
“…Similar to this study, the proportion of ulcers with a high risk for bleeding on second‐look endoscopy was reported to be 15.1% to 64.2% in several studies (Table ) . Even though patients in our study group were at high risk for post‐ESD bleeding, the proportion of ulcers with stabilized clean base was higher than that of other previous studies . Therefore, hemostatic powder application might be effective to stabilize the ulcer surface and prevent early bleeding in patients with larger resections.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Similar to this study, the proportion of ulcers with a high risk for bleeding on second‐look endoscopy was reported to be 15.1% to 64.2% in several studies (Table ) . Even though patients in our study group were at high risk for post‐ESD bleeding, the proportion of ulcers with stabilized clean base was higher than that of other previous studies . Therefore, hemostatic powder application might be effective to stabilize the ulcer surface and prevent early bleeding in patients with larger resections.…”
Section: Discussionsupporting
confidence: 82%
“…Third, second‐look endoscopy and prophylactic hemostasis might affect the bleeding rate. However, previous studies reported that second‐look endoscopy did not affect bleeding rates . Indeed, in our study, two patients had delayed bleeding events even though they underwent prophylactic hemostasis on second‐look endoscopy on POD 2.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations